Ethical Pressure, Organizational-Professional Conflict, and Related Work Outcomes among Management Accountants - Shafer, William E. (2002)
This study examines the effects of ethical pressure on management accountants' perceptions of organizational-professional conflict, and related work outcomes. It was hypothesized that organizational pressure to engage in unethical behavior would increase perceived organizational-professional conflict, and that this perceived conflict would reduce organizational commitment and job satisfaction, and increase the likelihood of employee turnover. A survey was mailed to a random sample of Certified Management Accountants to assess perceptions of the relevant variables. The results of a structural equations model indicated that, as hypothesized, ethical pressure was associated with higher levels of perceived organizational-professional conflict. Also as hypothesized, higher levels of conflict were associated with lower levels of organizational commitment and job satisfaction. Finally, lower levels of commitment and satisfaction were associated with higher turnover intentions.
Keywords: organizational-professional conflict; Organizational Commitment; Management accountants; ethical pressure